Online Dispute Resolution Berbasis Artificial Intelligence: Penyelesaian Sengketa Pinjaman Online Dalam Peer-To-Peer Lending - LATHFA ASHILA, NAJWA; PRANATA, KHAIQAL; MARDHIYAH, FATHONATUL (Fakultas Hukum, Universitas Palangka Raya, 2024)
Rapid technological developments affect various sectors of human life, including Financial Technology (FinTech) in the financial services sector. The presence of Fintech brings benefits to communities in connection with online loans in Peer-to-Peer Lending platforms which are increasingly being used. However, the large number of Peer-to-Peer Lending users is not matched by a clear dispute resolution mechanism, particularly concerning ‘Online Dispute Resolution’, This article aims to dissect the issues related to the implementation of Online Dispute Resolution for resolving dispute in Peer-to-Peer Lending online loans and to project the application of Artificial Intelligence based Online Dispute Resolution in addressing these issues. The research method used is the normative Judicial method, with data collected through a literature study. The data was processed using qualitative methods with legislative, comparative, and conceptual approaches. The research results show that implementing Online Dispute Resolution has several issues in resolving Peer-to-Peer Lending online loan disputes, both in terms of substance, structure, and legal culture. Therefore, one of the efforts that can be made to address this issue is to formulate and harmonize the implementation of Artificial Intelligence-based Online Dispute Resolution for resolving online Peer-to-Peer Lending loan disputes to create efficiency and effectiveness. The presence of an Online Dispute Resolution mechanism based on Artificial Intelligence is expected to fill the needs of society for justice.